Wielorównaniowy model ekonometryczny inflacji i bezrobocia w Polsce - Kisielińska, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
This paper presents a proposal for a multivariate model imaging relationship between inflation and unemployment in Poland. The model was estimated based on quarterly data. Then subjected them to statistical verification, which confirmed its accuracy. The model used to predict the recorded and expected inflation, and unemployment rate. Theoretical values were close to real values.